Ultrastructural Characteristics of Human Sperm After Cryopreservation with Polyvinylpiralidon by Vitrification - Hapon, Hanna O.; Pavlovich, Olena V.; Yurchuk, Taisiia O.; Repin, Mykola V.; Marchenko, Larysa M. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 178.